Practices underlying the accounting treatment of goodwill: the relevance of recognizing impairment losses and their impact on the results - Pousa, Soraia (2022)
Over the years, the accounting treatment of goodwill has undergone some changes, one of which being the most pertinent is the suspension of its systematic amortization, to become only the object of regular impairment tests, as its useful life was undefined. More recently, however, this accounting policy has resumed, that is, the subsequent measurement of goodwill considers its systematic amortization again. It is in this context that the present work is developed, whose main objective is to discuss the changes produced in the accounting treatment applicable in Portugal to goodwill in its subsequent recognition, essentially in terms of the relevance and sufficiency of the recognition of impairment losses and its impact on results. In order to answer it, a qualitative methodology was adopted, using content analysis applied to data collected from the 2014-2017 reports and accounts of a set of companies selected from the universe of companies in Portugal, listed and unlisted, among those in their balance sheets, under intangible assets, the goodwill equity element. In a complementary way, we also proposed to identify if the most recent reform introduced in the Portuguese regulations, with effect from 2016, produced significant changes. The results show that the recognition of impairment losses is low, mainly in unlisted companies, which is in line with the theory, and that the recent change in accounting standards also seems to be meaningless.